Psychological First Aid (PFA) Trainning For Teachers in Indonesia and Malaysia - Luky Kurniawan; Nanda Yunika Wulandari; Ruly Ningsih; Natri Sutanti (International Journal Of Community Service, 2022)
Psychological first aid (PFA) is an effort that can be done by anyone to provide appropriate support to survivors. Until now teachers still have difficulty in determining the role that needs to be done in providing psychological support to students in the event of a disaster. The purpose of this study was to increase the knowledge of teachers related to PFA giving. The activity was conducted on May 6 and 7, 2021. 540 participants are teachers participating in this workshop. On the first day, participants learn about the basic concepts of PFA, and on the second-day participants conducted P3L (Prepare, Look, Listen, and Link) applications in a Psychological First Aid (PFA) crisis accompanied by a facilitator. The results obtained were increased knowledge of Psychological First Aid (PFA) and how to apply it in the Education setting.